Optimalisasi Branding Posyandu Bahagia Dengan Canva Dalam Strategi Desain Grafis Untuk Promosi Dan Edukasi Kesehatan - Rian Maulana Yusup; Eti Wati; Windri Dewi Ayu; Ahmad Jaelani (JCS, 2025)
Posyandu Bahagia is one of the community health service centers in Cibeureuyeuh Village, Conggeng District, Sumedang Regency which has an important role in efforts to improve maternal and child health. However, in its implementation, this Posyandu faces challenges in terms of less than optimal communication and service promotion, which has an impact on low community participation in Posyandu activities. Therefore, this community service aims to optimize the branding of Posyandu Bahagia through the use of Canva as a graphic design tool in health promotion and education strategies. Using the Canva platform, which is easy to access and use, Posyandu members and health cadres in Cibeureuyeuh Village were trained to create various graphic design materials, such as informative and interesting posters, flyers and infographics. This approach is expected to increase the visibility of Posyandu Bahagia, increase public awareness of the importance of maternal and child health, and encourage higher participation in Posyandu activities. The methods used in this service activity are lectures, discussions and exercises. Apart from that, as a result of this, posyandu cadres realized that branding was needed as a distinctive characteristic and were interested in developing better branding. Thus, it can be said that this branding strategy received a positive response from Posyandu cadres.